Answer: The first option. (2,2)(3,1)(4,2)
Step-by-step explanation:
Is the following function an example
of exponential growth or decay?
f(x) = 198(0.73)x+1
Answer:
Exponential decay
Step-by-step explanation:
b = 0.73
Since the b is less than 1 (b<1), the rate is decreasing.
what equation represents the line that passes through (-8,11) and (4,7/2)
For this case we have that by definition, the equation of the line in slope-intersection form is given by:
[tex]y = mx + b[/tex]
Where:
m: It's the slope
b: It is the cutoff point with the y axis
We have:
[tex](x1, y1): (- 8,11)\\(x2, y2): (4,3.5)[/tex]
[tex]m = \frac {y2-y1} {x2-x1} = \frac {3.5-11} {4 - (- 8)} = \frac {-7.5} {4 + 8} = \frac {-7.5} {12 } = - \frac {\frac {15} {2}} {12} = - \frac {15} {24} = - \frac {5} {8}[/tex]
Thus, the equation will be given by:
[tex]y = - \frac {5} {8} x + b[/tex]
We substitute a point to find "b":
[tex]11 = - \frac {5} {8} (- 8) + b\\11 = 5 + b\\b = 11-5\\b = 6[/tex]
Finally:
[tex]y = - \frac {5} {8} x + 6[/tex]
Answer:
[tex]y = - \frac {5} {8} x + 6[/tex]
Answer:
So our answers could be any of these depending on the form wanted*:
[tex]y=\frac{-5}{8}x+6[/tex]
[tex]5x+8y=48[/tex]
[tex]y-11=\frac{-5}{8}(x+8)[/tex]
[tex]y-\frac{7}{2}=\frac{-5}{8}(x-4)[/tex]
*There are other ways to write this equation.
Step-by-step explanation:
So we are given two points on a line: (-8,11) and (4,7/2).
We can find the slope by using the formula [tex]\frac{y_2-y_1}{x_2-x_1} \text{ where } (x_1,y_1) \text{ and } (x_2,y+2) \text{ is on the line}[/tex].
So to do this, I'm going to line up my points vertically and then subtract vertically, then put 2nd difference over 1st difference:
( 4 , 7/2)
-(-8 , 11)
----------------
12 -7.5
So the slope is -7.5/12 or -0.625 (If you type -7.5 division sign 12 in your calculator).
-0.625 as a fraction is -5/8 (just use the f<->d button to have your calculator convert your decimal to a fraction).
Anyways the equation of a line in slope-intercept form is y=mx+b where m is the slope and b is y-intercept.
We have m=-5/8 since that is the slope.
So plugging this into y=mx+b gives us y=(-5/8)x+b.
So now we need to find b. Pick one of the points given to you (just one).
Plug it into y=(-5/8)x+b and solve for b.
y=(-5/8)x +b with (-8,11)
11=(-5/8)(-8)+b
11=5+b
11-5=b
6=b
So the equation of the line in slope-intercept form is y=(-5/8)x+6.
We can also put in standard form which is ax+by=c where a,b,c are integers.
y=(-5/8)x+6
First step: We want to get rid of the fraction by multiplying both sides by 8:
8y=-5x+48
Second step: Add 5x on both sides:
5x+8y=48 (This is standard form.)
Now you can also out the line point-slope form, [tex]y-y_1=m(x-x_1) \text{ where } m \text{ is the slope and } (x_1,y_1) \text{ is a point on the line }[/tex]
So you can say either is correct:
[tex]y-11=\frac{-5}{8}(x-(-8))[/tex]
or after simplifying:
[tex]y-11=\frac{-5}{8}(x+8)[/tex]
Someone might have decided to use the other point; that is fine:
[tex]y-\frac{7}{2}=\frac{-5}{8}(x-4)[/tex]
So our answers could be any of these depending on the form wanted*:
[tex]y=\frac{-5}{8}x+6[/tex]
[tex]5x+8y=48[/tex]
[tex]y-11=\frac{-5}{8}(x+8)[/tex]
[tex]y-\frac{7}{2}=\frac{-5}{8}(x-4)[/tex]
The sum of two numbers is 12, their product is 96. Compute these two numbers. Explain.
Answer:
The numbers are
[tex]6+2\sqrt{15}i[/tex] and [tex]6-2\sqrt{15}i[/tex]
Step-by-step explanation:
Let
x and y -----> the numbers
we know that
[tex]x+y=12[/tex] -----> [tex]y=12-x[/tex] ------> equation A
[tex]xy=96[/tex] ----> equation B
substitute equation A in equation B and solve for x
[tex]x(12-x)=96\\12x-x^{2}=96\\x^{2} -12x+96=0[/tex]
Solve the quadratic equation
The formula to solve a quadratic equation of the form [tex]ax^{2} +bx+c=0[/tex] is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]x^{2} -12x+96=0[/tex]
so
[tex]a=1\\b=-12\\c=96[/tex]
substitute
[tex]x=\frac{-(-12)(+/-)\sqrt{-12^{2}-4(1)(96)}} {2(1)}[/tex]
[tex]x=\frac{12(+/-)\sqrt{-240}} {2}[/tex]
Remember that
[tex]i^{2}=\sqrt{-1}[/tex]
[tex]x=\frac{12(+/-)\sqrt{240}i} {2}[/tex]
[tex]x=\frac{12(+/-)4\sqrt{15}i} {2}[/tex]
Simplify
[tex]x=6(+/-)2\sqrt{15}i[/tex]
[tex]x1=6+2\sqrt{15}i[/tex]
[tex]x2=6-2\sqrt{15}i[/tex]
we have two solutions
Find the value of y for the first solution
For [tex]x1=6+2\sqrt{15}i[/tex]
[tex]y=12-x[/tex]
substitute
[tex]y1=12-(6+2\sqrt{15}i)[/tex]
[tex]y1=6-2\sqrt{15}i[/tex]
Find the value of y for the second solution
For [tex]x2=6-2\sqrt{15}i[/tex]
[tex]y2=12-x[/tex]
substitute
[tex]y2=12-(6-2\sqrt{15}i)[/tex]
[tex]y2=6+2\sqrt{15}i[/tex]
therefore
The numbers are
[tex]6+2\sqrt{15}i[/tex] and [tex]6-2\sqrt{15}i[/tex]
Factor this expression completely. x2 + 6x + 9
Answer:
x² + 6x + 9 = (x + 3)(x + 3)
Step-by-step explanation:
It is given a quadratic equation
x² + 6x + 9
To find the factors of given expression
By using middle term splitting
Let f(x) = x² + 6x + 9
= x² + 3x + 3x + 9
= x(x + 3) + 3(x + 3)
= (x + 3)(x + 3)
Therefore the factors of x² + 6x + 9
(x + 3)(x + 3)
The expression [tex]\(x^2 + 6x + 9\)[/tex] factors completely to [tex]\((x + 3)^2\)[/tex].
To factor the expression [tex]\(x^2 + 6x + 9\)[/tex] completely, we can look for a pair of numbers that multiply to 9 (the constant term) and add up to 6 (the coefficient of the linear term).
The pair of numbers that satisfy these conditions is 3 and 3 because [tex]\(3 \times 3 = 9\) and \(3 + 3 = 6\).[/tex]
So, we can rewrite the expression as:
[tex]\[ x^2 + 3x + 3x + 9 \][/tex]
Now, we can group the terms:
[tex]\[ (x^2 + 3x) + (3x + 9) \][/tex]
Now, we can factor out the greatest common factor from each group:
[tex]\[ x(x + 3) + 3(x + 3) \][/tex]
Notice that both terms have a common factor of [tex]\(x + 3\)[/tex], so we can factor that out:
[tex]\[ (x + 3)(x + 3) \][/tex]
[tex]\[ (x + 3)^2 \][/tex]
Find the student's error in solving the following
inequality.
31 <-5x + 6
25 <-5x
-5
x>7
Step-by-step explanation:
when dividing by a (-)
the inequality sign changes
Answer:
"The student should have switched the direction of the inequality sign to get –5> x for a final answer."
and the second one is:
The student should have added 4 to all parts (left, middle, and right) to get 6 < –3x < 9.
Step-by-step explanation:
i got that on edge
Terry invested money in a biotech stock whose growth is modeled by the function f(x) = 0.01(2)x, where x represents number of days. Find the approximate average rate of change from day 2 to day 10.
Answer:
The average rate of change is 1.275
Step-by-step explanation:
The average rate of change of f(x) from x=a to x=b is given by:
[tex]\frac{f(b)-f(a)}{b-a}[/tex]
The money Terry invested is modeled by the function [tex]f(x)=0.01(2)^x[/tex] where x represents number of days.
The average rate of change from day 2 to day 10 is given by:
[tex]\frac{f(10)-f(2)}{10-2}[/tex]
[tex]f(10)=0.01(2)^{10}=10.24[/tex]
[tex]f(2)=0.01(2)^{2}=0.04[/tex]
The average rate of change becomes:
[tex]\frac{10.24-0.04}{8}[/tex]
[tex]=\frac{10.2}{8}=1.275[/tex]
Answer:
The average rate of change is 1.275
12(80-x)=816 what does x equal?
If x + y = 12 and x - y = 3, then
x2 - y2 =
[tex]x^2-y^2=(x-y)(x+y)\\\\x^2-y^2=3\cdot12=36[/tex]
What is the sign of 3xy when x>0 and y<0?
Let see.
Numbers which are bigger than 0 are defined as positive numbers and have a prefix of + (plus).
Numbers which are smaller than 0 are defined as negative numbers and have a prefix of - (minus).
Let say number a is equal to the expression,
[tex]a=3xy[/tex]
Since y is negative we can change its prefix to -,
[tex]a=3x\cdot(-y)[/tex]
Any number (in this case 3x) multiplied by negative number will produce a negative number.
Therefore the sign or prefix of number a will be -.
Hope this helps.
r3t40
When you multiply a positive number and a negative number, the result is a negative number. Therefore, the sign of 3xy, when x > 0 and y < 0, is negative.
Explanation:The question is asking for the sign of the product of two numbers, x and y, when x is positive (x > 0) and y is negative (y < 0). In mathematics, when you multiply a positive number and a negative number, the result is always a negative number.
So, the product of x and y or 3xy in this case, would be negative. This is due to the principle that the product of different signs (in this case, positive and negative) is always negative.
Learn more about Multiplication of positive and negative numbers here:https://brainly.com/question/34274159
#SPJ3
What is the value of x?
Enter your answer in the box
Answer:
25
Step-by-step explanation:
Those parallel lines tell us our triangles are similar. So that means the corresponding sides are proportional.
So we have that x corresponds to x+15 and
40 corresponds to 24+40.
So we have this proportion to solve:
[tex]\frac{x}{x+15}=\frac{40}{24+40}[/tex]
Let's simplify what we can:
[tex]\frac{x}{x+15}=\frac{40}{64}[/tex]
Cross multiply:
[tex](64)(x)=(x+15)(40)[/tex]
Multiply/distribute:
[tex]64x=40x+600[/tex]
Subtract 40x on both sides:
[tex]24x=600[/tex]
Divide both sides by 24:
[tex]x=\frac{600}{24}=25[/tex]
x=25
Answer:
x = 25.
Step-by-step explanation:
24/40 = 15/x
x = (40*15) / 24
x = 600/24
= 25.
Which polynomial is prime?
3x3 + 3x2 – 2x – 2
3x3 – 2x2 + 3x – 4
4x3 + 2x2 + 6x + 3
4x3 + 4x2 – 3x – 3
The prime polynomial out of the given options is 3x^3 + 3x^2 - 2x - 2.
Explanation:Out of the given polynomials, the polynomial that is prime is 3x3 + 3x2 - 2x - 2.
A polynomial is considered prime if it cannot be factored into a product of lower degree polynomials with integral coefficients.
In this case, the polynomial 3x3 + 3x2 - 2x - 2 is a cubic polynomial and cannot be factored further, so it is prime.
What is the value of the expression 10 − ( fraction 1 over 2 )4 ⋅ 48?
2
4
5
7
Answer:
The answer is 7
Step-by-step explanation:
The expression is 10-(1/2)^4 * 48
Here PEMDAS rule applies:
where,
P= parenthesis
E= exponent
M= multiplication
D= division
A= addition
S= subtraction
So according to this rule first we will solve parenthesis and exponent.(PE)
10-(1/2)^4 *48
(1/2)^4 means, multiply 1/2 four times:
1/2*1/2*1/2*1/2=1/16
Therefore the expression becomes:
10-1/16*48
Now we have MD which is multiplication and division:
1/16*48 = 3
Now after solving the multiplication and division the expression becomes:
10-3.
After subtracting the terms we have:
10-3=7
Thus the answer is 7....
Rationalize the denominator and simplify.
let's use the conjugate of the denominator and multiply top and bottom by it, recall the conjugate of a binomial is simply the same binomial with a different sign in between.
[tex]\bf \cfrac{2\sqrt{x}-3\sqrt{y}}{\sqrt{x}+\sqrt{y}}\cdot \cfrac{\sqrt{x}-\sqrt{y}}{\sqrt{x}-\sqrt{y}}\implies \cfrac{2\sqrt{x}\sqrt{x}-2\sqrt{x}\sqrt{y}~~-~~3\sqrt{x}\sqrt{y}+3\sqrt{y}\sqrt{y}}{\underset{\textit{difference of squares}}{(\sqrt{x}+\sqrt{y})(\sqrt{x}-\sqrt{y})}} \\\\\\ \cfrac{2\sqrt{x^2}-2\sqrt{xy}-3\sqrt{xy}+3\sqrt{y^2}}{(\sqrt{x})^2-(\sqrt{y})^2}\implies \cfrac{2x-5\sqrt{xy}+3y}{x-y}[/tex]
Answer:
[tex]\dfrac{2x-5\sqrt{xy}+3y}{x-y}\\[/tex]
Step-by-step explanation:
In Rationalize the denominator we multiply both numerator and denominator by the conjugate of denominator.
In Conjugate we change the sign of middle operator.
Example: Congugate of (a + b) = a - b
Now Solving the given expression,
[tex]\dfrac{2\sqrt{x} - 3\sqrt{y}}{\sqrt{x} + \sqrt{y}} = \dfrac{2\sqrt{x} - 3\sqrt{y}}{\sqrt{x} + \sqrt{y}}\times \dfrac{\sqrt{x} - \sqrt{y}}{\sqrt{x} - \sqrt{y}}\\\\\Rightarrow \dfrac{(2\sqrt{x} - 3\sqrt{y})(\sqrt{x} - \sqrt{y})}{( \sqrt{x} + \sqrt{y}){(\sqrt{x} - \sqrt{y}})}\ \ \ \ \ \ \ \ \ \ \ [\because (a-b)(a+b)=(a^{2} +b^{2})]\\\Rightarrow \dfrac{2x-2\sqrt{xy}-3\sqrt{xy}+3y}{x-y}\\\\ \Rightarrow \dfrac{2x-5\sqrt{xy}+3y}{x-y}\\[/tex]
Which equation represents the slope-intercept form of the line below?
Answer:
Choice B: y = 1/2x + 8
Step-by-step explanation:
Given
slope = 1/2
y-intercept = (0,8)
Put in y = mx + b form
slope is indicated by m
y-intercept is indicated by b
y = 1/2x + 8
Answer
y = 1/2x + 8
Answer: B. [tex]y=\dfrac{1}{2}x+8[/tex]
Step-by-step explanation:
We know that the equation of a line in slope-intercept form is given by :-
[tex]y=mx+c[/tex], where m is the slope of the line and c is the y-intercept of the line.
For the given graph , we have
y-intercept = (0,8)
i.e. c=8
Slope =[tex]\dfrac{1}{2}[/tex]
i.e. m=8
Then, the equation of the given line in slope-intercept form will be :-
[tex]y=\dfrac{1}{2}x+8[/tex]
given o below the arcs, wx and yz must be congruent.
Answer:
True.
Step-by-step explanation:
The arcs subtend the same equal angles at the center of the circle, i.e ∠YOZ=∠WOX= 27°. They are also bound by radii. All radii of the same circle are equal thus he two arcs are equal in length. OY= WO= XO= OZ
Therefore the two arcs wx and yz are congruent
Answer:
True
Step-by-step explanation:
just had the same question
Which value is equivalent to
[tex]\bf \left( \cfrac{~~\begin{matrix} 7 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~\cdot 5\cdot 2}{~~\begin{matrix} 7 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~\cdot 3} \right)^2 \times \left( \cfrac{5^0}{2^{-3}} \right)^3\times 2^{-9}\implies \left( \cfrac{5\cdot 2}{ 3} \right)^2 \times \left( \cfrac{1}{2^{-3}} \right)^3\times 2^{-9}[/tex]
[tex]\bf \left( \cfrac{10}{ 3} \right)^2 \times \left( 2^3 \right)^3\times 2^{-9}\implies \left( \cfrac{10}{ 3} \right)^2 \times 2^9\times 2^{-9}\implies \cfrac{10^2}{3^2}\times 2^{9-9} \\\\\\ \cfrac{100}{9}\times 2^0\implies \cfrac{100}{9}\times 1\implies \cfrac{100}{9}[/tex]
What is the scale factor of this dilation?
[Not drawn to scale]
The scale factor of the dilation is:
[tex]1\dfrac{1}{2}[/tex]
Step-by-step explanation:Scale factor--
It is a fixed amount by which the each of the dimension of the original figure is multiplied in order to obtain the dilated image of the figure.
Here we see that there is a enlargement dilation.
( since the side of the image increases after the dilation)
Let the scale factor be k.
From the figure we see that:
The side of length 6 units is transformed to get a side of length 9 units.
i.e.
[tex]6\times k=9[/tex]
i.e.
[tex]k=\dfrac{9}{6}\\\\i.e.\\\\k=\dfrac{3}{2}\\\\i.e.\\\\k=1\dfrac{1}{2}[/tex]
What is the following sum? Assume x > 0 and y > 0 sqrt x^2y^2+2 sqrt x^3y^4+xy sqrt y
Answer:
[tex]xy(1+2y\sqrt{x}+\sqrt{y})[/tex]
Step-by-step explanation:
Given expression,
[tex]\sqrt{x^2y^2}+2\sqrt{x^3y^4}+xy\sqrt{y}[/tex]
[tex]=(x^2y^2)^\frac{1}{2} + 2(x^3y^4)^\frac{1}{2} + xy\sqrt{y}[/tex]
[tex]\because (\sqrt{x}=x^\frac{1}{2})[/tex]
[tex]=(x^2)^\frac{1}{2} (y^2)^\frac{1}{2} + 2(x^3)^\frac{1}{2} (y^4)^\frac{1}{2} + xy\sqrt{y}[/tex]
[tex](\because (ab)^n=a^n b^n)[/tex]
[tex]=x^{2\times \frac{1}{2}} y^{2\times \frac{1}{2}} + 2(x^{3\times \frac{1}{2}})(y^{4\times \frac{1}{2}})+xy\sqrt{y}[/tex]
[tex]\because (a^n)^m=a^{mn}[/tex]
[tex]=x^1 y^1 + 2x^{1\frac{1}{2}} y^2 + xy\sqrt{y}[/tex]
[tex]=xy+2x.(x)^\frac{1}{2} y^2 + xy\sqrt{y}[/tex]
[tex]=xy+2xy^2\sqrt{x}+xy\sqrt{y}[/tex]
[tex]=xy(1+2y\sqrt{x}+\sqrt{y})[/tex]
Answer:
B is the right option
Step-by-step explanation:
On edg :))
Three red and three blue flags are arranged randomly along
a wire. What is the probability that the six flags alternate in
color?
A. 1/20
B. 1/10
C. 1/4
D. 1/2
[tex]|\Omega|=\dfrac{6!}{3!3!}=\dfrac{4\cdot5\cdot6}{2\cdot3}=20\\A=\{RBRBRB,BRBRBR\}\\|A|=2\\\\P(A)=\dfrac{2}{20}=\dfrac{1}{10}[/tex]
You are told that a sample of size 225 the mean is 48.5 and the standard deviation is 1.8 the study is reported with 90% confidence level explain how to determine if 48.8 is within the confidence interval
Answer with explanation:
Size of the sample = n =225
Mean[\text] \mu[/text]=48.5
Standard deviation [\text] \sigma[/text]= 1.8
[tex]Z_{90 \text{Percent}}=Z_{0.09}=0.5359\\\\Z_{score}=\frac{\Bar X -\mu}{\frac{\sigma}{\sqrt{\text{Sample size}}}}\\\\0.5359=\frac{\Bar X -48.5}{\frac{1.8}{\sqrt{225}}}\\\\0.5359=15 \times \frac{\Bar X -48.5}{1.8}\\\\0.5359 \times 1.8=15 \times (\Bar X -48.5)\\\\0.97=15 \Bar X-727.5\\\\727.5+0.97=15 \Bar X\\\\728.47=15 \Bar X\\\\ \Bar X=\frac{728.47}{15}\\\\\Bar X=48.57[/tex]
→Given Confidence Interval of Mean =48.8
→Calculated Mean of Sample =48.57 < 48.8
So, the value of Sample mean lies within the confidence interval.
Answer:
sample answer
Step-by-step explanation:
To find the margin of error, multiply the z-score by the standard deviation, then divide by the square root of the sample size.
The z*-score for a 90% confidence level is 1.645.
The margin of error is 0.20.
The confidence interval is 48.3 to 48.7.
48.8 is not within the confidence interval.
Suppose you and some friends are going to the movies. The amount of money you spend for tickets varies directly with the number of people buying
tickets. If you spend $48 for six tickets, what is the constant of variation?
e r song to the movies. The amount of money you spend for tckets vantes directly w
6
Answer:
The constant variation, and the price of one ticket is 8.
Step-by-step explanation:
Describe the steps you used to solve the equation and find the amount of Carrie’s allowance. Linear equation: 1 4 a + 1 3 a + 8 = 22
Sample Response: First, the like terms had to be combined using the lowest common denominator (LCD). Then the subtraction property of equality was used to isolate the variable term. Finally, both sides of the equation were multiplied by the reciprocal of the coefficient to solve for a.
The sum of a rational number and an irrational number equals:
Answer: is an irrational number
Step-by-step explanation:
Like adding three to pi (3.14159265358979323846264....)is still going to be irrational
Answer:
D
Step-by-step explanation:
I took the test
The temperature rose 9*F in three hours. If the starting temperature was -15*F what was the final temperature? Explain.
Answer:
-6*F
Step-by-step explanation:
-15+9=-6
How many deciliter are equivalent to 5 cups
Answer:
11.8294Step-by-step explanation:
Answer:
Step-by-step explanation:
How many deciliters are equivalent to 5 cups?
2.1097 deciliters
11.85 deciliters
118.5 deciliters
210.97 deciliters
ANSWER IS 11.85
A combination of a conditional statement and its converse written in the “if and only if” form. Both the conditional and the converse must be true before writing this statement .
Answer:
An angle is 90° if and only if it is a right angle.
Explanation:
The statement is: If an angle is 90°, then it is a right angle.
The converse of this statement would be:
If an angle is a right angle, it is 90°.
Clearly, both the conditional and converse of this statement is true.
Does anyone know how to do this ? Please help !
Ah, all you have to do is combine 2/5m and 3/5m.
In this case:
=2/5m - 4/5 - 3/5m
=-1/5m - 4/5
=-m/5-4/5
Answer:
[tex]\frac{-1}{5}m-\frac{4}{5}[/tex]
Step-by-step explanation:
You are given:
[tex]\frac{2}{5}m-\frac{4}{5}-\frac{3}{5}m[/tex]
Reorder using commutative property (putting like terms together):
[tex]\frac{2}{5}m-\frac{3}{5}m-\frac{4}{5}[/tex]
Now we are going to bring down the -4/5 (there is nothing to do there).
(2/5)m and -(3/5)m have the same denominator all we have to do is figure out what is 2-3 which is -1
[tex]\frac{-1}{5}m-\frac{4}{5}[/tex]
If the length of one leg of a right triangle is 3 and the hypotenuse is [tex]\sqrt{34}[/tex], what is the length of the other leg?
[tex]\huge{\boxed{5}}[/tex]
The Pythagorean theorum states that when [tex]a[/tex] and [tex]b[/tex] are sides and [tex]c[/tex] is the hypotenuse, [tex]a^2 + b^2 = c^2[/tex]
So, let's plug in the values. [tex]3^2 + b^2 = (\sqrt{34})^2[/tex]
Simplify. The square of a square root is the number inside the square root. [tex]9 + b^2 = 34[/tex]
Subtract 9 from both sides. [tex]b^2 = 25[/tex]
Get the square root of both sides. [tex]\sqrt{b^2} = \sqrt{25}[/tex]
[tex]b=\boxed{5}[/tex]
Answer:
5Step-by-step explanation:
Use the Pythagorean theorem:
[tex]leg^2+leg^2=hypotenuse^2[/tex]
We have
[tex]leg=3,\ hypotenuse=\sqrt{34}[/tex]
Let's mark the other leg as x.
Substitute:
[tex]3^2+x^2=(\sqrt{34})^2[/tex] use (√a)² = a
[tex]9+x^2=34[/tex] subtract 9 from both sides
[tex]x^2=25\to x=\sqrt{25}\\\\x=5[/tex]
If f(x) = sqrt (4x+9) +2 which inequality can be used to find the domain of f(x)
Answer:
Step-by-step explanation:
the domain of x represents the values that x can be without the function being undefined. the function of square rooting is undefined for negative numbers. so in order to find the domain, you must ensure that the "stuff" in the square root is greater than, or equal, to zero. hence, (4x+9)>= 0. the answer is B
For this case we have the following function:
[tex]f (x) = \sqrt {4x + 9} +2[/tex]
By definition, the domain of a function is given by all the values for which the function is defined.
For the given function to be defined, then the root argument must be positive, that is:
[tex]4x + 9 \geq0[/tex]
Answer:
Option B
Suppose f(x) = x^2. What is the graph of g(x) =f(4x)?
Answer:
your y-intercept is 0 and slope is 4 so any line with zero slope it will be horizontal
Answer: On mine it is D
Step-by-step explanation:
It is the small one facing up